Etnobotani Bambu di Kecamatan Darul Imarah Kabupaten Aceh Besar - Hendra Ervany; Djufri Djufri; Abdullah Abdullah (Universitas Islam Negeri Ar-Raniry, 2020)
A study on Bamboo Ethnobotany has been conducted at Darul Imarah, Aceh Besar on June 10, 2010 to June 20, 2010. The aims of this study are to determine the types of bamboo and its utilization at Darul Imarah, Aceh Besar. The method used is observation. The data analyzed in this study were descriptive and displayed in figures and tables form. The parameters observed were the types of bamboo plants and its utilization by the people of Darul Imarah, Aceh Besar. The results showed that there were 6 types of bamboo at Darul Imarah, Aceh Besar, namely Bambusa arundinacea and Dendrocalamus asper, as their use for making household furniture and other building materials. The type of Bambusa vulgaris used from its bamboo shoots as a treatment for hepatitis. Types of Bambusa ventricosa and Dracaena surculosa are used as ornamental plants and home gardening plants. Type of Scizostachyum branchycladum which is used for making lemang. There are four genera namely Bambusa, Dendrocalamus, Scizotachyum, and Dracaena. The dominant type of bamboo that grows in the Darul Imarah, Aceh Besar is the Bambusa arundinacea type.